2016
DOI: 10.1037/ccp0000122
|View full text |Cite
|
Sign up to set email alerts
|

Brief mindfulness training reduces salivary IL-6 and TNF-α in young women with depressive symptomatology.

Abstract: Objective Pro-inflammatory cytokines have been implicated in the pathophysiology and maintenance of depression. This study investigated the effects of a brief mindfulness intervention on salivary pro-inflammatory correlates of depression (IL-6, TNF-α) and self-reported symptoms of depression in college women. Methods Sixty-four females with a cut score of ≥ 16 on the Center for Epidemiological Studies for Depression Scale (CES-D) were assigned to a 4-week mindfulness-based intervention (MBI; N=31) or a conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 61 publications
(88 reference statements)
5
40
0
1
Order By: Relevance
“…The small sample size precluded further adjusting. (b) Individuals trained in mindfulness will show less pro-inflammatory dysregulation 35,62 . To test this hypothesis, we used random intercept models including each cell-type/humoral and arm data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small sample size precluded further adjusting. (b) Individuals trained in mindfulness will show less pro-inflammatory dysregulation 35,62 . To test this hypothesis, we used random intercept models including each cell-type/humoral and arm data.…”
Section: Methodsmentioning
confidence: 99%
“…Other randomised trials of community samples also failed to find effects on CRP 35,59 and cell counts 60 , although mindfulness meditation significantly influenced TNF-α levels in healthy individuals when individual studies were combined in a meta-analysis. Trials on clinically anxious or depressed populations found significant effects on TNF-α with samples of 60-70 participants 61,62 ; however a recent actively controlled trial with HIV patients failed to find any effects 63,27 .…”
Section: Outcome (Unit)mentioning
confidence: 97%
“…In a randomized clinical trial in MDD patients, results showed that serum IL-6 levels, as well as depression severity, significantly decreased after 16 sessions of supportive-expressive dynamic psychotherapy [123]. It was found that after individual mindfulness training, the salivary IL-6 levels had decreased, which was maintained for 3 months, in a study testing the application of brief mindfulness intervention in young women with depressive symptomatology [124]. One small scale study with 11 women in the first episode of depression treated with cognitive behavioral therapy alone demonstrated that cognitive behavioral therapy reduced both depressive symptoms and the serum IL-6 levels [125].…”
Section: Psychological Interventionsmentioning
confidence: 99%
“…Third, salivary cytokines are associated with several somatic disease conditions (e.g., asthma, rheumatoid arthritis, cardiovascular disease, diabetes, and cancer; Zhang et al, 2016) in addition to depressive symptoms (Keller, El-Sheikh, Vaughn, & Granger, 2010). Finally, intervention studies have shown that salivary cytokine levels subside during mindfulness training for depression (Walsh, Eisenlohr-Moul, & Baer, 2016).…”
Section: Inflammation and Depressionmentioning
confidence: 99%